Random differential equations in science and engineering - Soong, T. T.; ScienceDirect eBooks (New York : Academic Press, 1973)
Random differential equations in science and engineering.
Front Cover; Random Differential Equations in Science and Engineering; Copyright Page; Contents; Preface; Acknowledgments; Chapter 1. Introduction; Chapter 2. Probability and Random Variables: A Review; Chapter 3. Stochastic Processes and Their Classifications; Chapter 4. Stochastic Limits and Calculus in Mean Square; Chapter 5. Random Ordinary Differential Equations; Chapter 6. Differential Equations with Random Initial Conditions; Chapter 7. Differential Equations with Random Inhomogeneous Parts; Chapter 8. Differential Equations with Random Coefficients; Chapter 9. Stochastic Stability.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Differential equations; MATHEMATICS -- Differential Equations -- General; Differential equations; Electronic books